Negative electrode for lithium secondary battery, method for manufacturing negative electrode for lithium secondary battery, and lithium secondary battery comprising negative electrode

By using the double -layer active material layer structure on the negative electrode of the lithium secondary battery, the high content SiOX and multiple active materials are used to solve the reduction of the capacity of the silicon compound on the negative electrode Battery performance.

CN119384728APending Publication Date: 2025-01-28LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380050870.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-26
Filing Date
2023-12-13
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

When using silicon-based compounds as the negative electrode active material of lithium secondary battery, the capacity characteristics are reduced and the battery cycle performance is poor, especially the deterioration of the electrode surface during the charge and discharge cycle.

Method used

The two -layer negative active material layer structure is adopted. Among them, the first negative active material layer contains high -content Siox, and the second negative active material layer contains carbon, silicon and metal active materials. Thickness to ensure the uniformity and thinness of the second negative polar active material layer.

Benefits of technology

While maintaining high -capacity and high density characteristics, prevent the surface of the electrode, improve the circulation performance, and form more uniform and thin coating to extend the life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119384728A_ABST
    Figure CN119384728A_ABST
Patent Text Reader

Abstract

The present application relates to a negative electrode, a method of manufacturing the same, and a lithium secondary battery comprising the same, the negative electrode comprising: a negative electrode current collector layer; a first negative electrode active material layer provided on one surface or both surfaces of the negative electrode current collector layer; and a second negative electrode active material layer formed on the first negative electrode active material layer, in which the second negative electrode active material layer satisfies a non-uniformity of Formula 1 below. [Formula 1] 0 [mu] m < = | C-(A + B) / 2 | < = 10 [mu] m (In Formula 1, A represents the longest distance ([mu] m) between the first surface and the second surface, B represents the shortest distance ([mu] m) between the first surface and the second surface, and C represents the average thickness ([mu] m) of the second negative electrode active material layer).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims priority to and the benefit of Korean Patent Application No. 10-2022-0184859 filed in the Korean Intellectual Property Office on December 26, 2022, the entire contents of which are incorporated herein by reference.

[0002] Accordingly, the present application relates to a negative electrode for a lithium secondary battery, a method for manufacturing a negative electrode for a lithium secondary battery, and a lithium secondary battery including the negative electrode. Background Art

[0003] Because the use of fossil fuels is rapidly increasing, there is an increasing demand for the use of alternative energy or clean energy, and as part of this, the most active field of research is the field of power generation and storage using electrochemical reactions.

[0004] Currently, secondary batteries are representative examples of electrochemical devices utilizing such electrochemical energy, and the scope of use thereof tends to gradually expand.

[0005] With the technological development and increase in demand for mobile devices, the demand for secondary batteries as energy sources has increased rapidly. Among these secondary batteries, lithium secondary batteries with high energy density and voltage, long cycle life and low self-discharge rate have been commercialized and widely used. In addition, as electrodes for such high-capacity lithium secondary batteries, methods for manufacturing high-density electrodes with higher energy density per unit volume are being actively studied.

[0006] Generally, a secondary battery includes a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode includes a negative electrode active material for inserting and extracting lithium ions from the positive electrode, and as the negative electrode active material, silicon-based particles having a high discharge capacity can be used.

[0007] In particular, in recent years, as a response to the demand for high-density energy batteries, a method of increasing capacity by using silicon-based compounds such as Si / C or SiOx, which have a capacity more than 10 times that of graphite-based materials, as negative electrode active materials in a combined manner is being actively studied. However, when compared with commonly used graphite, silicon-based compounds as high-capacity materials have excellent capacity characteristics themselves, but undergo rapid volume expansion during charging and disconnect the conductive path, resulting in deterioration of battery characteristics, and accordingly, the capacity begins to decrease from the initial stage. In addition, for silicon-based negative electrodes, when the charge and discharge cycle is repeated, lithium ions are charged unevenly in the depth direction of the negative electrode and the reaction proceeds on the surface, thereby accelerating the degradation in the surface, so it is necessary to improve performance in terms of battery cycles.

[0008] Therefore, in order to solve the problems that occur when silicon-based compounds are used as negative electrode active materials, various methods have been discussed, such as a method of controlling the driving potential, a method of additionally coating a thin film on the active material layer, a method of suppressing the volume expansion of itself such as a method of controlling the particle size of the silicon-based compound, or developing a binder that can suppress the volume expansion of the silicon-based compound to prevent disconnection of the conductive path. In addition, research is being conducted to limit the proportion of the silicon-based active material used during the initial charge and discharge by pre-lithiation of the silicon-based active material layer and to impart a storage effect, thereby supplementing the life characteristics of the silicon-based negative electrode.

[0009] However, because the above method may deteriorate the performance of the battery, the application is limited, and thus there are still limitations in the commercialization of manufacturing negative electrode batteries with a high content of silicon-based compounds. In addition, as the proportion of silicon-based active materials contained in the silicon-based active material layer increases, pre-lithiation will be concentrated on the surface of the negative electrode, which will damage the silicon-based active materials on the surface, and due to the uneven pre-lithiation, there are problems in improving the life characteristics.

[0010] Therefore, a method of using a silicon-based active material and a negative electrode active material layer as a buffer layer is also being studied. However, adding any thinner film on top of the silicon-based active material layer that is formed thinly for fast charging is very difficult in terms of process, making it difficult to manufacture through actual processes and products.

[0011] Therefore, it is necessary to study a method that does not cause a decrease in capacity characteristics even when a silicon-based compound is used as an active material in order to improve capacity characteristics, and can improve cycle performance by preventing degradation of the electrode surface during charge and discharge cycles, and can form a more uniform and thinner coating even when a double-layer active material layer is used.

[0012] Prior art literature

[0013] (Patent Document 1) Japanese Patent Application Publication No. 2009-080971 Summary of the invention

[0014] [Technical issues]

[0015] The present application relates to a negative electrode for a lithium secondary battery, a method for manufacturing a negative electrode for a lithium secondary battery, and a lithium secondary battery comprising the negative electrode, wherein the negative electrode for a lithium secondary battery is capable of maximizing capacity characteristics when a silicon-based active material is used for the negative electrode, which is the main purpose of using the silicon-based active material; and preventing degradation of the electrode surface during charge and discharge cycles, which is a problem in the prior art; in addition, a uniform double-layer negative electrode active material layer and a thin film coating can be achieved to ensure fast charging performance and processability.

[0016] [Technical solution]

[0017] An exemplary embodiment of the present specification provides a negative electrode for a lithium secondary battery, the negative electrode comprising: a negative electrode collector layer; a first negative electrode active material layer, the first negative electrode active material layer being disposed on one surface or both surfaces of the negative electrode collector layer; and a second negative electrode active material layer, the second negative electrode active material layer being disposed on a surface of the first negative electrode active material layer opposite to a surface facing the negative electrode collector layer, wherein the first negative electrode active material layer contains a first negative electrode active material layer composition containing a first negative electrode active material, and the second negative electrode active material layer contains a second negative electrode active material layer composition containing a second negative electrode active material, wherein the first negative electrode active material contains one or more selected from the group consisting of SiOx (x=0) and SiOx (0<x<2), and based on 100 parts by weight of the first negative electrode active material, 95 parts by weight or more of SiOx is contained. (x=0), wherein the second negative electrode active material comprises one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of forming an alloy with lithium, and a lithium-containing nitride, wherein the second negative electrode active material layer has a first surface of the second negative electrode active material layer opposite to a surface facing the first negative electrode active material layer and a second surface of the second negative electrode active material layer facing the first negative electrode active material layer, wherein the first surface and the second surface respectively comprise an uneven surface, and wherein the second negative electrode active material layer satisfies the unevenness represented by the following Formula 1:

[0018] [Formula 1]

[0019] 0 μm≤│C-(A+B) / 2│≤10 μm

[0020] In the above formula 1,

[0021] A represents the longest distance between the first surface and the second surface (μm),

[0022] B represents the shortest distance between the first surface and the second surface (μm), and

[0023] C represents the average thickness (μm) of the second negative electrode active material layer.

[0024] Another exemplary embodiment provides a method for manufacturing a negative electrode for a lithium secondary battery, the method comprising: preparing a negative electrode current collector layer; forming a first negative electrode active material layer by coating a first negative electrode active material layer composition onto one surface or both surfaces of the negative electrode current collector layer; and forming a second negative electrode active material layer by coating a second negative electrode active material layer composition onto the surface of the first negative electrode active material layer opposite to the surface in contact with the negative electrode current collector layer, wherein the first negative electrode active material comprises one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the first negative electrode active material, comprises 95 parts by weight or more of SiOx (x = 0), wherein the second negative electrode active material comprises one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of forming an alloy with lithium, and a lithium-containing nitride, wherein in the step of forming the first negative electrode active material layer by coating the first negative electrode active material layer composition, the liquid thickness of the coater is 50 μm or more and 100 μm or less, and wherein in the step of forming the second negative electrode active material layer by coating the second negative electrode active material layer composition onto the surface of the first negative electrode active material layer opposite to the surface in contact with the negative electrode current collector layer, the liquid thickness of the coater is 10 μm or more and 60 μm or less.

[0025] Finally, a lithium secondary battery is provided, the lithium secondary battery comprising: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator disposed between the positive electrode and the negative electrode; and an electrolyte.

[0026] Advantageous Effects

[0027] The negative electrode for a lithium secondary battery according to an exemplary embodiment of the present invention has a double-layer active material layer composed of a first negative electrode active material layer and a second negative electrode active material layer. In particular, the first negative electrode active material contained in the first negative electrode active material layer comprises one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the first negative electrode active material, comprises 95 parts by weight or more of SiOx (x = 0), and the second negative electrode active material contained in the second negative electrode active material layer comprises one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of forming an alloy with lithium, and a lithium-containing nitride.

[0028] The negative electrode for a lithium secondary battery according to the present application comprises a double-layer active material layer having a specific composition and content as described above. In particular, the first negative electrode active material layer comprises a high content of SiOx (x=0), so that the advantages of high capacity, high density and fast charging can be maintained as is. In addition, silicon-based and / or carbon-based active materials, etc. are included in the second negative electrode active material layer, so that the degradation of the electrode surface during the charge and discharge cycle can be prevented, and the uniformity can also be improved during pre-lithiation.

[0029] In particular, in the negative electrode for a lithium secondary battery according to the present application, the second negative electrode active material layer satisfies the non-uniformity of the above formula 1. In other words, the first negative electrode active material layer has a silicon-based negative electrode and is coated within a thin thickness range. In this case, there is a problem when the second negative electrode active material layer is formed in the form of a thin film on the silicon-based negative electrode. However, when coated by the method in the present application (by controlling the liquid thickness and core thickness of the coater), the non-uniformity of the above formula 1 is satisfied, and the second negative electrode active material layer can be more uniformly and thinly coated on the first negative electrode active material layer.

[0030] Therefore, a lithium secondary battery including the negative electrode satisfies the optimum capacity characteristics, which is an advantage of the Si negative electrode, and at the same time satisfies the cycle characteristics.

[0031] Therefore, the negative electrode for a lithium secondary battery according to the present application has the following characteristics: the second negative electrode active material layer is more uniformly and thinly coated in the form of a film on the first negative electrode active material layer to construct a double layer, thereby utilizing the advantages of applying high-content Si particles as a single-layer active material to the electrode while solving the problems of surface degradation, uniformity during pre-lithiation and life characteristics, which are disadvantages when applying high-content Si particles to the electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 is a diagram showing a stacked structure of a negative electrode for a lithium secondary battery according to an exemplary embodiment of the present application.

[0033] Figure 2 is a diagram showing a stacked structure of a negative electrode for a lithium secondary battery according to an exemplary embodiment of the present application.

[0034] Figure 3 It is a diagram showing a SEM photograph of a negative electrode for a lithium secondary battery according to an exemplary embodiment of the present application.

[0035] Figure 4 is a flow chart showing a wet-on-dry process according to an exemplary embodiment of the present application.

[0036] Figure 5 is a flow chart showing a wet-on-wet process according to an exemplary embodiment of the present application.

[0037] <Description of symbols>

[0038] 10: Second negative electrode active material layer

[0039] 20: First negative electrode active material layer

[0040] 30: Negative electrode collector layer

[0041] 100: Negative electrode for lithium secondary battery DETAILED DESCRIPTION

[0042] Before describing the present invention, some terms are first defined.

[0043] In the present specification, when a part “includes,” “contains,” or “has” a constituent element, unless otherwise specifically stated, this does not mean that other constituent elements are excluded but means that other constituent elements may further be included.

[0044] In this specification, "p to q" means a range of "p or more and q or less".

[0045] In this specification, "specific surface area" is measured by the BET method, specifically, calculated from the nitrogen adsorption at liquid nitrogen temperature (77 K) using BELSORP-mini II manufactured by BEL Japan. That is, in this application, the BET specific surface area may refer to the specific surface area measured by the above measurement method.

[0046] In this manual, "D n " refers to the particle size distribution, and refers to the particle size at the n% point of the cumulative distribution of the number of particles according to the particle size. That is, D 50 D is the particle size at the 50% point of the cumulative distribution of particle numbers according to the particle size (average particle size, center particle size), 90 is the particle size at the 90% point of the cumulative distribution of particle numbers according to particle size, and D 10 It is the particle size at the 10% point of the cumulative distribution of the number of particles according to the particle size. On the other hand, the particle size distribution can be measured using a laser diffraction method. Specifically, after the powder to be tested is dispersed in a dispersion medium, the prepared dispersion is introduced into a commercially available laser diffraction particle size determination device (e.g., Microtrac S3500), wherein the difference in the diffraction pattern according to the particle size is determined when the laser beam passes through the particles, and then the particle size distribution is calculated.

[0047] In the present specification, the description "a polymer contains a specific monomer as a monomer unit" means that the monomer participates in a polymerization reaction and is contained in the polymer as a repeating unit. In the present specification, when a polymer contains a monomer, it is interpreted as the same as that the polymer contains the monomer as a monomer unit.

[0048] In this specification, it should be understood that the term "polymer" is used in a broad sense, including copolymers, unless otherwise explicitly referred to as a "homopolymer".

[0049] In this specification, the weight average molecular weight (M w ) and number average molecular weight (M n ) is a polystyrene-converted molecular weight measured by gel permeation chromatography (GPC) using commercially available monodisperse polystyrene polymers (standard samples) with various polymerization degrees for measuring molecular weight as standard materials. In this specification, unless otherwise specifically stated, molecular weight refers to weight average molecular weight.

[0050] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings so that those skilled in the art can easily implement the present invention. However, the present invention can be implemented in various forms and is not limited to the following description.

[0051] An exemplary embodiment of the present specification provides a negative electrode for a lithium secondary battery, the negative electrode comprising: a negative electrode collector layer; a first negative electrode active material layer, the first negative electrode active material layer being disposed on one surface or both surfaces of the negative electrode collector layer; and a second negative electrode active material layer, the second negative electrode active material layer being disposed on a surface of the first negative electrode active material layer opposite to a surface facing the negative electrode collector layer, wherein the first negative electrode active material layer contains a first negative electrode active material layer composition containing a first negative electrode active material, and the second negative electrode active material layer contains a second negative electrode active material layer composition containing a second negative electrode active material, wherein the first negative electrode active material contains one or more selected from the group consisting of SiOx (x=0) and SiOx (0<x<2), and based on 100 parts by weight of the first negative electrode active material, 95 parts by weight or more of SiOx is contained. (x=0), wherein the second negative electrode active material comprises one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of forming an alloy with lithium, and a lithium-containing nitride, wherein the second negative electrode active material layer has a first surface of the second negative electrode active material layer opposite to a surface facing the first negative electrode active material layer and a second surface of the second negative electrode active material layer facing the first negative electrode active material layer, wherein the first surface and the second surface respectively comprise an uneven surface, and wherein the second negative electrode active material layer satisfies the unevenness represented by the following Formula 1:

[0052] [Formula 1]

[0053] 0 μm≤│C-(A+B) / 2│≤10 μm

[0054] In formula 1,

[0055] A represents the longest distance between the first surface and the second surface (μm),

[0056] B represents the shortest distance between the first surface and the second surface (μm), and

[0057] C represents the average thickness (μm) of the second negative electrode active material layer.

[0058] In the negative electrode for lithium secondary batteries according to the present application, the second negative electrode active material layer satisfies the non-uniformity of the above formula 1. In other words, the first negative electrode active material layer has a silicon-based negative electrode and is coated within a thin thickness range. In this case, there is a problem when the second negative electrode active material layer is formed in the form of a thin film on the silicon-based negative electrode. However, when coated by the method in the present application (by controlling the liquid thickness and core thickness of the coating machine), the non-uniformity of the above formula 1 is satisfied, and the second negative electrode active material layer can be more uniformly and thinly coated on the first negative electrode active material layer. In other words, the negative electrode for lithium secondary batteries according to the present application optimizes the uniformity and thickness of the first negative electrode active material layer and the second negative electrode active material layer, the first negative electrode active material layer has a high capacity feature, and the second negative electrode active material layer can control the problem of the non-uniformity of the reaction in which the first negative electrode active material layer reacts only on the electrode surface during charge and discharge and the problem of uniformity during pre-lithiation, and has excellent durability. Therefore, a lithium secondary battery including the negative electrode satisfies the optimum capacity characteristics, which is an advantage of the Si negative electrode, and at the same time satisfies the lifespan characteristics.

[0059] Figure 1 1 is a diagram showing a stacked structure of a negative electrode for a lithium secondary battery according to an exemplary embodiment of the present application. Specifically, it can be seen that the negative electrode 100 for a lithium secondary battery includes a first negative electrode active material layer 20 and a second negative electrode active material layer 10 on one surface of a negative electrode collector layer 30 . Figure 1 It is shown that the first negative electrode active material layer is formed on one surface, but the first negative electrode active material layer may be formed on both surfaces of the negative electrode collector layer. As described above, in the exemplary embodiment of the present application, the first negative electrode active material layer may be formed on the entire surface of the negative electrode collector layer, and the second negative electrode active material layer may be formed on the entire surface of the first negative electrode active material layer.

[0060] also, Figure 2 is a diagram showing a stacking structure of a negative electrode for a lithium secondary battery according to an exemplary embodiment of the present application. In particular, Figure 2As shown, the first negative electrode active material layer 20 and the second negative electrode active material layer 10 can be formed on both surfaces of the negative electrode current collector layer 30. In addition, an arrangement of 10>20>30>20>10 is possible. Additionally, for example, 10>20>30>20, 10>20>30>10, 10>20>30>10>20, etc. When the first negative electrode active material layer and the second negative electrode active material layer are sequentially stacked on only one surface of the negative electrode current collector layer, the negative electrode active material layers can be stacked in any arrangement on the opposite surface. Preferably, both surfaces of the negative electrode current collector layer have the same composition, and specifically, a structure of 10>20>30>20>10 can be provided.

[0061] Hereinafter, the negative electrode for a lithium secondary battery of the present invention will be described in more detail.

[0062] In an exemplary embodiment of the present application, a negative electrode for a lithium secondary battery is provided, the negative electrode including: a negative electrode current collector layer; a first negative electrode active material layer disposed on one or both surfaces of the negative electrode current collector layer; and a second negative electrode active material layer disposed on a surface of the first negative electrode active material layer opposite to the surface in contact with the negative electrode current collector layer.

[0063] In an exemplary embodiment of the present application, the negative electrode current collector layer generally has a thickness of 1 μm to 100 μm. There is no particular limitation on such a negative electrode current collector layer as long as it has high electrical conductivity and does not cause chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, fired carbon can be used; copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc.; aluminum-cadmium alloy, etc. In addition, the negative electrode current collector layer may have fine irregularities formed on the surface to enhance the binding force of the negative electrode active material, and can be used in various forms such as films, sheets, foils, meshes, porous bodies, foams, and non-woven fabric bodies.

[0064] In an exemplary embodiment of the present application, the thickness of the negative electrode current collector layer can be 1 μm or more and 100 μm or less.

[0065] However, the thickness can be variously changed according to the type and use of the negative electrode used, and is not limited thereto.

[0066] In an exemplary embodiment of the present application, the first negative electrode active material may include one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the first negative electrode active material, 95 parts by weight or more of SiOx (x = 0) may be included.

[0067] In an exemplary embodiment of the present application, the first negative electrode active material may include one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the first negative electrode active material, it may include 95 parts by weight or more, preferably 97 parts by weight or more, more preferably 99 parts by weight or more and 100 parts by weight or less of SiOx (x = 0).

[0068] In an exemplary embodiment of the present application, pure silicon (Si) particles may be particularly used as the first negative electrode active material. Using pure silicon (Si) as the first negative electrode active material may mean that, as described above, based on a total of 100 parts by weight of the first negative electrode active material, pure Si particles (SiOx (x = 0)) that are not bound to other particles or elements within the above range are included.

[0069] In an exemplary embodiment of the present application, the first negative electrode active material may be composed of SiOx (x = 0).

[0070] The first negative electrode active material layer according to the present application contains the first negative electrode active material, specifically, pure silicon particles containing 95 parts by weight or more of SiOx (x = 0). When a high content of pure silicon particles is included, the capacity characteristics are excellent, but the life characteristics deteriorate due to uneven reactions on the surface. Therefore, the second negative electrode active material layer according to the present invention is included in a specific weight loading amount, thereby solving the above problems.

[0071] It should be noted that the average particle diameter (D 50 ) of the first negative electrode active material of the present invention may be 3 μm to 10 μm, specifically 4 μm to 8 μm, and more specifically 5 μm to 7 μm. When the average particle diameter is within the above range, the specific surface area of the particles is within an appropriate range, thereby forming the viscosity of the negative electrode slurry within an appropriate range. Therefore, the particles constituting the negative electrode slurry are smoothly dispersed. In addition, when the size of the first negative electrode active material has a value equal to or greater than the lower limit value of the above range, since the conductive material and the binder form a complex in the negative electrode slurry, the contact area between the silicon particles and the conductive material is excellent, so the possibility of the continuous conductive network increases, thereby improving the capacity retention rate. On the other hand, when the average particle diameter satisfies the above range, excessive silicon particles are excluded, so that the surface of the formed negative electrode is smooth. Therefore, it is possible to prevent the uneven phenomenon of the current density during charge and discharge.

[0072] In an exemplary embodiment of the present application, the first negative electrode active material generally has a characteristic BET specific surface area. The BET specific surface area of the first negative electrode active material is preferably 0.01 m 2 / g to 150.0 m 2 / g, and more preferably 0.1 m 2 / g to 100.0m 2 / g, particularly preferably 0.2 m 2 / g to 80.0 m 2 / g, and most preferably 0.2 m 2 / g to 18.0 m 2 / g. The BET specific surface area is measured according to DIN 66131 (using nitrogen).

[0073] In an exemplary embodiment of the present application, the first negative electrode active material may be present, for example, in a crystalline or amorphous form, and is preferably not porous. The silicon particles are preferably spherical or fragmentary particles. Alternatively, but less preferably, the silicon particles may also have a fibrous structure or may be present in the form of a film or coating containing silicon.

[0074] In the exemplary embodiment of the present application, the first negative electrode active material may have a non-spherical shape and its sphericity (roundness) is, for example, 0.9 or less, for example, 0.7 to 0.9, for example, 0.8 to 0.9, for example, 0.85 to 0.9.

[0075] In the present application, sphericity is determined by the following formula A-1, where A is the area and P is the boundary line.

[0076] [Formula A-1]

[0077] 4πA / P 2

[0078] In an exemplary embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the content of the first negative electrode active material is 60 parts by weight or more based on 100 parts by weight of the first negative electrode active material layer composition.

[0079] In another exemplary embodiment, the content of the first negative electrode active material may be 60 parts by weight or more, preferably 65 parts by weight or more, more preferably 70 parts by weight or more, and 95 parts by weight or less, preferably 90 parts by weight or less, more preferably 80 parts by weight or less, based on 100 parts by weight of the first negative electrode active material layer composition.

[0080] Although the first negative electrode active material layer composition according to the present application uses a first negative electrode active material with a significantly high capacity within the above-mentioned range, since the following second negative electrode active material layer is also used, the problems of surface degradation during charging and discharging, uniformity in the pre-lithiation process, and life characteristics are solved without reducing the overall capacity performance of the negative electrode.

[0081] In the related art, only graphite compounds are usually used as negative electrode active materials. However, in recent years, as the demand for high-capacity batteries increases, attempts to mix and use silicon compounds to increase capacity have increased. However, the limitation of silicon compounds is that the volume expands rapidly during charge and discharge, resulting in damage to the conductive path formed in the negative electrode active material layer, thereby deteriorating the performance of the battery.

[0082] Accordingly, in the exemplary embodiment of the present application, the first negative electrode active material layer composition may further include one or more selected from the group consisting of a first negative electrode conductive material and a first negative electrode binder.

[0083] In this case, as the first negative electrode conductive material and the first negative electrode binder included in the first negative electrode active material layer composition, materials used in the art may be used without limitation.

[0084] In the exemplary embodiment of the present application, as the first negative electrode conductive material, materials commonly used in the art may be used without limitation, and specifically may include one or more selected from the group consisting of point conductive materials, planar conductive materials, and linear conductive materials.

[0085] In the exemplary embodiment of the present application, the point-shaped conductive material refers to a conductive material that can be used to improve the conductivity of the negative electrode, has conductivity without causing chemical changes, and has a point-shaped or spherical shape. Specifically, the point-shaped conductive material can be one or more species selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide, and polyphenylene derivatives, and in terms of achieving high conductivity and excellent dispersibility, carbon black may be preferably included.

[0086] In an exemplary embodiment of the present application, the dot-shaped conductive material may have a thickness of 40 m 2 / g and above 70 m 2 / g or less, preferably 45 m 2 / g and above 65 m 2 / g or less and more preferably 50 m 2 / g and above 60 m 2 / g or less BET specific surface area.

[0087] In an exemplary embodiment of the present application, the particle size of the dot-shaped conductive material may be 10 nm to 100 nm, preferably 20 nm to 90 nm, and more preferably 20 nm to 60 nm.

[0088] In the exemplary embodiment of the present application, the first negative electrode conductive material may include a planar conductive material.

[0089] The planar conductive material can be used to improve conductivity by increasing surface contact between silicon particles in a negative electrode while suppressing disconnection of a conductive path due to volume expansion, and may be in the form of a plate-shaped conductive material or a bulk-type conductive material.

[0090] In the exemplary embodiment of the present application, the planar conductive material may include one or more selected from the group consisting of plate-like graphite, graphene, graphene oxide, and graphite flakes, and may preferably be plate-like graphite.

[0091] In the exemplary embodiment of the present application, the average particle size (D 50 ) may be 2 μm to 7 μm, specifically 3 μm to 6 μm, and more specifically 4 μm to 5 μm. When the average particle size satisfies the above range, sufficient particle size results in easy dispersion without causing excessive increase in viscosity of the negative electrode slurry. Therefore, when the same equipment and time are used for dispersion, the dispersion effect is excellent.

[0092] In an exemplary embodiment of the present application, a negative electrode composition is provided, wherein the planar conductive material has a D 10 , D greater than 2.5 μm and less than 3.5 μm 50 and D of 7.0 μm or more and 15.0 μm or less 90 .

[0093] In the exemplary embodiment of the present application, as for the planar conductive material, a high specific surface area planar conductive material having a high BET specific surface area or a low specific surface area planar conductive material may be used.

[0094] In the exemplary embodiment of the present application, for the planar conductive material, a planar conductive material with a high specific surface area or a planar conductive material with a low specific surface area can be used without limitation. However, in particular, the planar conductive material according to the present application may affect the electrode performance to a certain extent due to the dispersion effect, so it is particularly preferred to use a planar conductive material with a low specific surface area that does not cause dispersion problems.

[0095] In an exemplary embodiment of the present application, the planar conductive material may have a thickness of 5 m 2 / g or more BET specific surface area.

[0096] In another exemplary embodiment, the planar conductive material may have a 5 m 2 / g and above 500 m 2 / g or less, preferably 5 m 2 / g and above 300 m 2 / g or less, more preferably 5 m2 / g and above 250 m 2 / g or less BET specific surface area.

[0097] In another exemplary embodiment, the planar conductive material is a high specific surface area planar conductive material, and the BET specific surface area may satisfy 50 m 2 / g and above 500 m 2 / g or less, preferably 80 m 2 / g and above 300 m 2 / g or less, more preferably 100 m 2 / g and above 300 m 2 / g or less.

[0098] In another exemplary embodiment, the planar conductive material is a low specific surface area planar conductive material, and the BET specific surface area may satisfy 5 m 2 / g and above 40 m 2 / g or less, preferably 5 m 2 / g or more and 30 m 2 / g or less, more preferably 5 m 2 / g and above 25 m 2 / g or less.

[0099] Other conductive materials may include linear conductive materials such as carbon nanotubes. The carbon nanotubes may be bundle-type carbon nanotubes. The bundle-type carbon nanotubes may include a plurality of carbon nanotube units. Specifically, unless otherwise specified, the term "bundle-type" herein refers to a bundle or rope-like secondary shape in which a plurality of carbon nanotube units are arranged side by side or entangled in a manner in which the longitudinal axes of the carbon nanotube units are substantially oriented in the same direction. The carbon nanotube units have a cylindrical graphene sheet with a nanometer-scale diameter and have a sp 2 Bonding structure. In this case, depending on the curling angle and structure of the graphene sheet, the characteristics of a conductor or a semiconductor can be displayed. Compared with entangled carbon nanotubes, bundled carbon nanotubes can be more evenly dispersed during the negative electrode manufacturing process, and can more smoothly form a conductive network in the negative electrode to improve the conductivity of the negative electrode.

[0100] In an exemplary embodiment of the present application, the first negative electrode conductive material may satisfy a range of 10 parts by weight or more and 40 parts by weight or less based on 100 parts by weight of the first negative electrode active material layer composition.

[0101] In another exemplary embodiment, the content of the first negative electrode conductive material may be 1 part by weight or more and 40 parts by weight or less, preferably 3 parts by weight or more and 30 parts by weight or less, and more preferably 5 parts by weight or more and 25 parts by weight or less, based on 100 parts by weight of the first negative electrode active material layer composition.

[0102] In an exemplary embodiment of the present application, the first negative electrode conductive material may include a dot conductive material, a planar conductive material, and a linear conductive material, and a ratio of dot conductive material:planar conductive material:linear conductive material may satisfy 1:1:0.01 to 1:1:1.

[0103] In an exemplary embodiment of the present application, the dot-shaped conductive material may satisfy a range of 1 part by weight or more and 60 parts by weight or less, preferably 5 parts by weight or more and 50 parts by weight or less, and more preferably 10 parts by weight or more and 50 parts by weight or less, based on 100 parts by weight of the first negative electrode conductive material.

[0104] In an exemplary embodiment of the present application, the planar conductive material may satisfy a range of 1 part by weight or more and 60 parts by weight or less, preferably 5 parts by weight or more and 50 parts by weight or less, and more preferably 10 parts by weight or more and 50 parts by weight or less, based on 100 parts by weight of the first negative electrode conductive material.

[0105] In an exemplary embodiment of the present application, the linear conductive material may satisfy a range of 0.01 parts by weight or more and 10 parts by weight or less, preferably 0.05 parts by weight or more and 8 parts by weight or less, and more preferably 0.1 parts by weight or more and 5 parts by weight or less, based on 100 parts by weight of the first negative electrode conductive material.

[0106] In the exemplary embodiment of the present application, the first negative electrode conductive material may include a linear conductive material and a planar conductive material.

[0107] In the exemplary embodiment of the present application, the first negative electrode conductive material may include a linear conductive material and a planar conductive material, and a weight ratio of the linear conductive material to the planar conductive material may satisfy 0.01:1 to 0.1:1.

[0108] In the exemplary embodiment of the present application, because the first negative electrode conductive material satisfies the above composition and ratio, the life characteristics of the existing lithium secondary battery will not be greatly affected and the points at which the battery can be charged and discharged are increased, so the first negative electrode conductive material has the characteristic of excellent output characteristics at a high C rate.

[0109] The first negative electrode conductive material according to the present application has a completely different structure from the conductive material applied to the positive electrode. That is, the first negative electrode conductive material according to the present application is used to maintain contact between the silicon-based active material whose volume expansion is very large due to charge and discharge, while the positive electrode conductive material is used to act as a buffer during rolling while imparting some conductivity, and is completely different from the negative electrode conductive material of the present invention in structure and function.

[0110] In addition, the first negative electrode conductive material according to the present application is applied to the silicon-based active material and has a completely different configuration from the conductive material applied to the graphite-based active material. That is, because the conductive material used for the electrode with the graphite-based active material has only smaller particles than the active material, the conductive material has the characteristics of improving the output characteristics and imparting some conductivity, and is completely different in structure and function from the first negative electrode conductive material applied together with the silicon-based active material in the present invention.

[0111] In an exemplary embodiment of the present application, the first negative electrode binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and the above materials in which hydrogen is replaced by Li, Na, Ca, etc., and may also include various copolymers thereof.

[0112] The first negative electrode binder according to the exemplary embodiment of the present application is used to retain the first negative electrode active material and the first negative electrode conductive material to prevent the first negative electrode active material from volume expansion and distortion and structural deformation of the negative electrode structure during relaxation. When these functions are met, all general-purpose binders can be used. Specifically, an aqueous binder can be used, and more specifically, a PAM-based binder can be used.

[0113] In an exemplary embodiment of the present application, based on 100 parts by weight of the first negative electrode active material layer composition, the content of the first negative electrode binder may be 30 parts by weight or less, preferably 25 parts by weight or less, more preferably 20 parts by weight or less, and may be 5 parts by weight or more, 10 parts by weight or more.

[0114] Compared with the existing carbon-based negative electrode, when using a Si-based negative electrode, applying the aqueous binder in the above weight parts enables the use of a dot-shaped conductive material. In addition, the above characteristics make the dot-shaped conductive material hydrophobic and the bonding strength between the conductive material and the binder excellent.

[0115] In the exemplary embodiment of the present application, the second negative electrode active material may include one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of forming an alloy with lithium, and a lithium-containing nitride.

[0116] In another exemplary embodiment, the second negative electrode active material may include one or more and three or less selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of forming an alloy with lithium, and a lithium-containing nitride.

[0117] In another exemplary embodiment, the second negative electrode active material may include a carbon-based active material and a silicon-based active material.

[0118] In another exemplary embodiment, the second negative electrode active material may include a silicon-based active material.

[0119] In an exemplary embodiment of the present application, a negative electrode for a lithium secondary battery is provided, wherein the second negative electrode active material includes one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of forming an alloy with lithium, and a lithium-containing nitride, and based on 100 parts by weight of the second negative electrode active material, the content of the silicon-based active material is 50 parts by weight or more and 100 parts by weight or less.

[0120] In another exemplary embodiment, the second negative electrode active material may include one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of forming an alloy with lithium, and a lithium-containing nitride, and based on 100 parts by weight of the second negative electrode active material, the content of the silicon-based active material may be 50 parts by weight or more and 100 parts by weight or less, preferably 70 parts by weight or more and 100 parts by weight or less, and more preferably 80 parts by weight or more and 100 parts by weight or less.

[0121] In an exemplary embodiment of the present application, the silicon-based active material included in the second negative electrode active material may include one or more selected from the group consisting of SiOx (0 < x < 2), SiC, and Si alloy.

[0122] In an exemplary embodiment of the present application, the silicon-based active material included in the second negative electrode active material may include one or more selected from the group consisting of SiOx (0 < x < 2), SiC, and Si alloy, and based on 100 parts by weight of the second negative electrode active material, it may include 1 part by weight or more of SiOx (0 < x < 2).

[0123] In another exemplary embodiment, the silicon-based active material included in the second negative electrode active material may include one or more selected from the group consisting of SiOx (0 < x < 2), SiC, and Si alloy, and based on 100 parts by weight of the second negative electrode active material, it may include 1 part by weight or more or 10 parts by weight or more and 99 parts by weight or less of SiOx (0 < x < 2).

[0124] In another exemplary embodiment, the silicon-based active material included in the second negative electrode active material may include SiOx (0 <x<2)。

[0125] In another exemplary embodiment, the silicon-based active material included in the second negative electrode active material may include SiC.

[0126] The negative electrode for lithium secondary battery according to the present application contains the second negative electrode active material in the second negative electrode active material layer as described above. Therefore, while maintaining high capacity and high density characteristics by including the first negative electrode active material, the second negative electrode active material acts as a buffer layer, thereby solving the problem of surface degradation during charge and discharge, the problem of uniformity during pre-lithiation, and the problem of life characteristics.

[0127] As an example, the second negative electrode active material layer of the present application can be used as a buffer layer. Compared with electrodes containing SiO or carbon-based active materials, electrodes containing Si active materials have excellent capacity characteristics. However, in electrodes containing Si active materials, degradation is concentrated on the surface of the negative electrode active material layer due to rapid reaction with Li ions during charge and discharge. This also occurs in a pre-lithiation process in which lithium ions are pre-included in the negative electrode active material layer. In the pre-lithiation process, a buffer layer is used to prevent direct contact between the Si-based electrode and lithium and to prevent surface degradation. Therefore, the second negative electrode active material layer of the present invention has the characteristic of being able to exhibit the same action and effect as the buffer layer in the pre-lithiation process.

[0128] In the exemplary embodiment of the present application, representative examples of carbon-based active materials include natural graphite, artificial graphite, expandable graphite, carbon fiber, difficult-graphitizable carbon, carbon black, carbon nanotubes, fullerenes, activated carbon, etc., and the carbon-based active materials can be used without limitation, as long as the carbon-based active materials are generally used for carbon materials for lithium secondary batteries, and specifically can be processed into a spherical or dot-like shape and used.

[0129] In the exemplary embodiment of the present application, the planar conductive material used as the first negative electrode conductive material is different in structure and function from the carbon-based active material generally used as the negative electrode active material. Specifically, the carbon-based active material used as the negative electrode active material may be artificial graphite or natural graphite, and refers to a material processed into a spherical or dot-like shape and used to facilitate the storage and release of lithium ions.

[0130] On the other hand, the planar conductive material used as the first negative electrode conductive material is a material having a planar or plate-like shape, and may be in the form of plate-like graphite. That is, the planar conductive material is a material included to maintain a conductive path in the negative electrode active material layer, and refers to a material that ensures a conductive path in a planar shape inside the negative electrode active material layer, rather than a material that plays a role in storing and releasing lithium.

[0131] That is, in the present application, using plate-like graphite as a conductive material means processing graphite into a planar or plate-like shape and using it as a material that ensures a conductive path rather than a material that plays a role in storing or releasing lithium. In this case, the negative electrode active material contained together has a high capacity characteristic in terms of storing and releasing lithium, and plays a role in storing and releasing all lithium ions transferred from the positive electrode.

[0132] On the other hand, in the present application, using a carbon-based active material as an active material means that the carbon-based active material is processed into a dot-like or spherical shape and used as a material for storing or releasing lithium.

[0133] That is, in the exemplary embodiment of the present application, the artificial graphite or natural graphite as the carbon-based active material may have a carbon content satisfying 0.1 m 2 / g and above 4.5 m 2 / g or less. In addition, plate-like graphite as a planar conductive material has a planar shape, and its BET specific surface area can be 5 m 2 / g or above.

[0134] Representative examples of metal-based active materials may be metal substances containing any one or two or more metal elements selected from the group consisting of Al, Sn, Ag, Bi, Mg, Zn, In, Ge, Pb, Pd, Pt, Ti, Sb, Ga, Mn, Fe, Co, Ni, Cu, Sr, and Ba. These metal substances may be used in any form such as simple substance, alloy, oxide (TiO2, SnO2, etc.), nitride, sulfide, boride, and alloy with lithium, but simple substance, alloy, oxide, and alloy with lithium may increase capacity.

[0135] In an exemplary embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein a content of the second negative electrode active material is 60 parts by weight or more based on 100 parts by weight of the second negative electrode active material layer composition.

[0136] In another exemplary embodiment, the content of the second negative electrode active material may be 60 parts by weight or more, 100 parts by weight or less, or 99 parts by weight or less, based on 100 parts by weight of the second negative electrode active material layer composition.

[0137] The second negative electrode active material layer composition according to the present application has the characteristic of suppressing the surface reaction of the negative electrode to enhance the life characteristics without deteriorating the capacity performance of the negative electrode by using a second negative electrode active material with lower capacity characteristics than the first negative electrode active material but less particle breakage during charge and discharge within the above range.

[0138] In an exemplary embodiment of the present application, a negative electrode for a lithium secondary battery is provided, wherein the second negative electrode active material layer composition further includes one or more selected from the group consisting of a second negative electrode conductive material and a second negative electrode binder.

[0139] In this case, the description about the second negative electrode conductive material and the second negative electrode binder may be the same as the above description about the first negative electrode conductive material and the first negative electrode binder.

[0140] In an exemplary embodiment of the present application, the second negative electrode active material layer has a first surface of the second negative electrode active material layer opposite to a surface facing the first negative electrode active material layer and a second surface of the second negative electrode active material layer facing the first negative electrode active material layer, and the first surface and the second surface respectively include uneven surfaces.

[0141] In this case, the fact that the first surface and the second surface respectively include uneven surfaces means that the surfaces or interfaces are not ideally formed to be straight without concavities and convexities but include some concavities and convexities and curves.

[0142] That is, generally, when the composition is applied, the surface or interface thereof is not formed to be ideally straight but is formed to have an uneven shape, which can be interpreted to mean that the first surface and the second surface include uneven surfaces.

[0143] Figure 3 It is a figure showing a SEM photograph of a negative electrode for a lithium secondary battery according to an exemplary embodiment of the present application. Specifically, the surface marked with a red dashed line (triangular mark) corresponds to the second surface of the second negative electrode active material layer, and the surface marked with a yellow dashed line (circular mark) corresponds to the first surface. In this case, the inclusion of an uneven surface may mean that the yellow and red dashed lines do not form a straight line but include a curve.

[0144] In an exemplary embodiment of the present application, a negative electrode for a lithium secondary battery is provided, wherein the second negative electrode active material layer satisfies the non-uniformity represented by Formula 1 below.

[0145] [Formula 1]

[0146] 0 μm≤│C-(A+B) / 2│≤10 μm

[0147] In formula 1,

[0148] A represents the longest distance between the first surface and the second surface (μm),

[0149] B represents the shortest distance between the first surface and the second surface (μm), and

[0150] C represents the average thickness (μm) of the second negative electrode active material layer.

[0151] In the exemplary embodiment of the present application, A represents the longest distance (μm) between the first surface and the second surface. Specifically, A may represent the longest distance among all perpendicular distances between the first surface and the second surface in the thickness direction.

[0152] In the exemplary embodiment of the present application, B represents the shortest distance (μm) between the first surface and the second surface. Specifically, B may represent the shortest distance among all perpendicular distances between the first surface and the second surface in the thickness direction.

[0153] Furthermore, C is a value measured by averaging all perpendicular distances between the first surface and the second surface in the thickness direction, and is defined as the average thickness of the second negative electrode active material layer.

[0154] In the present application, when the first negative electrode active material layer and the second negative electrode active material layer are ideally coated, the first surface and the second surface are both formed as uniform surfaces, and the values ​​of A and B may be the same. That is, it may mean that the first surface and the second surface are uniformly formed in the form of the same shortest distance and the same longest distance. In this case, if both the first negative electrode active material layer and the second negative electrode active material layer are uniformly coated, the shortest distance, the longest distance, and the average thickness of the second negative electrode active material layer all have the same value, and the above formula 1 satisfies the value of 0.

[0155] In the exemplary embodiment of the present application, the second negative electrode active material layer satisfying the range of Formula 1 above may mean that the second negative electrode active material layer is more uniformly coated on the first negative electrode active material layer.

[0156] In an exemplary embodiment of the present application, the above Formula 1 may satisfy 0 μm≤│C-(A+B) / 2│≤10 μm, preferably 0.5 μm≤│C-(A+B) / 2│≤8 μm, and more preferably 0.5 μm≤│C-(A+B) / 2│≤5 μm.

[0157] In an exemplary embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, in which A is 5 μm or more and 25 μm or less, and C is 5 μm or more and 20 μm or less.

[0158] In the exemplary embodiment of the present application, A may satisfy the range of 5 μm or more and 25 μm or less, preferably 5.5 μm or more and 20 μm or less, and more preferably 6 μm or more and 19 μm or less.

[0159] In the exemplary embodiment of the present application, B may satisfy the range of 3 μm or more and 10 μm or less, preferably 4 μm or more and 9 μm or less, and more preferably 7 μm or more and 9 μm or less.

[0160] In the exemplary embodiment of the present application, C may satisfy the range of 5 μm or more and 20 μm or less, preferably 5.5 μm or more and 18 μm or less, and more preferably 6 μm or more and 15 μm or less.

[0161] In particular, in the negative electrode for lithium secondary batteries according to the present application, the second negative electrode active material layer satisfies the non-uniformity of the above formula 1. In other words, the first negative electrode active material layer has a silicon-based negative electrode and is coated within a thin thickness range. In this case, there is a problem in forming the second negative electrode active material layer in the form of a thin film on the silicon-based negative electrode. However, when coated by the following method (by controlling the liquid thickness and core thickness of the coater), the non-uniformity of the above formula 1 is satisfied, and the second negative electrode active material layer can be more uniformly and thinly coated on the first negative electrode active material layer. Therefore, fast charging performance can be ensured while ensuring life characteristics by effectively controlling surface degradation reactions.

[0162] In an exemplary embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein an average thickness of the second negative electrode active material layer is 10% or more and 40% or less of the total thickness of the first negative electrode active material layer and the second negative electrode active material layer.

[0163] In another exemplary embodiment, the thickness of the first negative electrode active material layer may be 10 μm or more and 200 μm or less, specifically 15 μm or more and 190 μm or less, and more specifically 20 μm or more and 170 μm or less.

[0164] In an exemplary embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein an average surface roughness (Sa) of the first surface is 700 nm or less.

[0165] In another exemplary embodiment, the average surface roughness (Sa) of the first surface may be 700 nm or less, preferably 680 nm or less, more preferably 660 nm or less, and may be 400 nm or more, preferably 500 nm or more, more preferably 600 nm or more.

[0166] In an exemplary embodiment of the present application, the average surface roughness may refer to surface roughness. The average surface roughness indicates the degree of roughness of a surface and may indicate the degree of unevenness of a surface of a target material.

[0167] In an exemplary embodiment of the present application, a negative electrode for a lithium secondary battery is provided, wherein the viscosity of the first negative electrode active material layer composition is a shear viscosity of 2,000 cPs or more and 15,000 cPs or less at a shear rate of 2.5 (1 / s), and the viscosity of the second negative electrode active material layer composition is lower than the viscosity of the first negative electrode active material layer composition.

[0168] In another exemplary embodiment, the viscosity of the first negative active material layer composition may satisfy a shear viscosity of 2,000 cPs to 15,000 cPs, preferably 2,300 cPs to 14,000 cPs, more preferably 2,500 cPs to 12,000 cPs at a shear rate of 2.5 (1 / s).

[0169] In this case, the viscosity of the second negative electrode active material layer composition should be kept lower than the viscosity of the first negative electrode active material layer composition so that a double negative electrode active material layer can be formed as in the present application. More specifically, the viscosity of the second negative electrode active material layer composition should be lower than but similar to the viscosity of the first negative electrode active material layer composition.

[0170] In the exemplary embodiment of the present application, the negative electrode for a lithium secondary battery may be pre-lithiated.

[0171] The negative electrode for lithium secondary battery according to the present application is composed of double layers. In particular, the second negative electrode active material layer satisfying specific heterogeneity acts as a buffer layer in the pre-lithiation process, so that uniform lithiation occurs in the depth direction of the electrode during the charge and discharge cycle.

[0172] An exemplary embodiment of the present application provides a method for manufacturing a negative electrode for a lithium secondary battery, the method comprising: preparing a negative electrode collector layer; applying a first negative electrode active material layer composition to one surface or both surfaces of the negative electrode collector layer by a coating machine to form a first negative electrode active material layer; and applying a second negative electrode active material layer composition to a surface of the first negative electrode active material layer opposite to a surface contacting the negative electrode collector layer by a coating machine to form a second negative electrode active material layer, wherein the first negative electrode active material comprises one or more selected from the group consisting of SiOx (x=0) and SiOx (0<x<2), and based on 100 parts by weight of the first negative electrode active material, comprises 95 parts by weight or more of SiOx (x=0), wherein the second negative electrode active material comprises one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of forming an alloy with lithium, and a lithium-containing nitride, wherein in the step of forming the first negative electrode active material layer by coating the first negative electrode active material layer composition, the liquid thickness of the coating machine is 50 μm or more and 100 μm or more. μm or less, and wherein in the step of forming the second negative active material layer by applying the second negative active material layer composition to the surface of the first negative active material layer opposite to the surface contacting the negative current collector layer, the liquid thickness of the coater is 10 μm or more and 60 μm or less.

[0173] In the method of manufacturing the negative electrode, the above description may be applied to the composition and content included in each step.

[0174] That is, each composition is coated by a coating machine to form a first negative electrode active material layer and a second negative electrode active material layer as described above. In this case, it is found that when the liquid thickness of the coating machine as described above is met, the second negative electrode active material layer can be thinly and evenly coated on the first negative electrode active material layer in the form of a film. Therefore, it is possible to manufacture a negative electrode for a lithium secondary battery that satisfies the above formula 1.

[0175] In the exemplary embodiment of the present application, the liquid thickness of the coater may have the same meaning as the thickness of the coating liquid, and may refer to the liquid thickness of the coated first negative electrode active material layer composition or the second negative electrode active material layer composition itself.

[0176] In an exemplary embodiment of the present application, there is provided a method of manufacturing a negative electrode for a lithium secondary battery, wherein a core thickness of a coater is 0.4T or more and 2T or less.

[0177] The present invention applies a second negative electrode active material layer that can play the advantages of pure Si active material and make up for its shortcomings to the first negative electrode active material layer. In particular, the second negative electrode active material layer should be implemented in the form of a thin film coating. However, it is a difficult task to thinly and evenly coat the second negative electrode active material layer on the thin first negative electrode active material layer. However, as described above, it is found that when the liquid thickness and core thickness of the coater are adjusted to the above range, a negative electrode for a lithium secondary battery that meets the uniformity and thickness according to the present application can be manufactured.

[0178] The exemplary embodiment of the present application includes forming the first negative active material layer by coating the first negative active material layer composition on one surface or both surfaces of the negative current collector layer by a coating machine.

[0179] That is, this step is a step of forming an active material layer on the negative electrode current collector layer, and may refer to a step of forming the active material layer on the surface (lower layer portion) in contact with the negative electrode current collector layer in the double-layer structure.

[0180] In the exemplary embodiment of the present application, the coating of the first negative electrode active material layer composition includes coating and drying the first negative electrode slurry including the first negative electrode active material layer composition and a negative electrode slurry solvent.

[0181] In this case, the solid content of the first negative electrode slurry may satisfy a range of 10% to 40%.

[0182] In an exemplary embodiment of the present application, the formation of the first negative electrode active material layer may include: mixing a first negative electrode slurry; and coating the mixed first negative electrode slurry on one surface or both surfaces of the negative electrode collector layer by a coater, and the coating may be performed using a coating method commonly used in the art.

[0183] The exemplary embodiment of the present application includes forming the second negative active material by applying the second negative active material layer composition to a surface of the first negative active material layer opposite to a surface contacting the negative current collector layer by a coater.

[0184] That is, this step is a step of forming the second negative electrode active material layer on the first negative electrode active material layer, and may refer to a step of forming the active material layer on the surface (upper layer portion) away from the negative electrode collector layer in the double-layer structure.

[0185] In the exemplary embodiment of the present application, the coating of the second negative electrode active material layer composition includes coating and drying the second negative electrode slurry including the second negative electrode active material layer composition and a negative electrode slurry solvent.

[0186] In this case, the solid content of the second negative electrode slurry may satisfy the range of 10% to 40%.

[0187] In an exemplary embodiment of the present application, a method for manufacturing a negative electrode for a lithium secondary battery is provided, wherein forming a second negative electrode active material layer may include: mixing a second negative electrode slurry; and coating the mixed second negative electrode slurry on a surface of the first negative electrode active material layer opposite to a surface contacting the negative electrode collector layer.

[0188] The coating can be performed using a coating method commonly used in the art.

[0189] The description of the formation of the first negative electrode active material layer may be similarly applied to the formation of the second negative electrode active material layer.

[0190] In an exemplary embodiment of the present application, a method of manufacturing a negative electrode for a lithium secondary battery is provided, wherein forming a second negative electrode active material layer on a first negative electrode active material layer may include a wet-on-dry process or a wet-on-wet process.

[0191] In the exemplary embodiment of the present application, the wet-on-dry process may refer to a process of coating a first negative electrode active material layer composition, partially or completely drying the composition, and coating a second negative electrode active material layer composition on the composition.

[0192] Figure 4 is a flow chart showing a wet-cover-dry process according to an exemplary embodiment of the present application. Specifically, in the wet-cover-dry process, a first negative electrode slurry mixture (a first negative electrode active material, a first negative electrode conductive material, a first negative electrode binder, a first solvent) is prepared and applied to the negative electrode collector layer. Thereafter, the first negative electrode slurry mixture is dried to form a first negative electrode active material layer. Then, a second negative electrode slurry mixture is prepared, applied to the first negative electrode active material layer, and dried to form a second negative electrode active material layer. Thereafter, the individual layers may be rolled and pressed to form a negative electrode for a lithium secondary battery according to the present application.

[0193] In the exemplary embodiment of the present application, the wet-on-wet process refers to a process of coating a first negative electrode active material layer composition and coating a second negative electrode active material layer composition thereon without drying the first negative electrode active material layer composition.

[0194] Figure 5 is a flow chart showing a wet-on-wet process according to an exemplary embodiment of the present application. Specifically, in the wet-on-wet process, a first negative electrode slurry mixture is prepared and applied to a negative electrode current collector layer, while a second negative electrode slurry mixture is prepared and applied to the first negative electrode slurry mixture, and then the first and second negative electrode slurry mixtures are dried. Thereafter, each layer may be rolled and pressed to form a negative electrode for a lithium secondary battery according to the present application.

[0195] Thereafter, the negative electrode formed according to the wet-on-dry process or the wet-on-wet process may be cut twice using a single coating die.

[0196] In particular, the wet-to-dry process is to apply the first negative electrode active material layer composition, completely dry the composition, and then apply the second negative electrode active material layer composition thereon, so that the first negative electrode active material layer and the second negative electrode active material layer can have a clear boundary through the above process. Therefore, the components contained in the first negative electrode active material layer and the second negative electrode active material layer are not mixed, so that a double layer can be constructed.

[0197] In the exemplary embodiment of the present application, the negative electrode slurry solvent may be used without limitation as long as it can dissolve the first negative electrode active material layer composition and the second negative electrode active material layer composition, and specifically, water or NMP may be used.

[0198] As a result of the wet-on-wet process described above, a junction region in which the first negative electrode active material layer and the second negative electrode active material layer are mixed may be formed. In this case, in order to perform the wet-on-wet process, the viscosity of the first negative electrode active material layer composition should be lower than the viscosity of the second negative electrode active material layer composition so that mutual mixing occurs in the junction region and process.

[0199] In the present application, after the first negative electrode active material layer is dried (wet-cover-dry process), the second negative electrode active material layer is formed, so that the interface between the two layers is clearly distinguished. In addition, when the second negative electrode active material layer is applied when the first negative electrode active material layer composition is not completely dried (the first negative electrode active material layer composition and the second negative electrode active material layer composition are applied at the same time), mixing occurs at the interface of the two layers to form a bonding area.

[0200] In an exemplary embodiment of the present application, a method for manufacturing a negative electrode for a lithium secondary battery is provided, the method comprising pre-lithiation of a negative electrode having a first negative electrode active material layer and a second negative electrode active material layer formed on a negative electrode collector layer, wherein the pre-lithiation of the negative electrode comprises a lithium plating process, a lithium metal transfer process, a lithium metal deposition process, or a stabilized lithium metal powder (SLMP) coating process.

[0201] As described above, the second negative electrode active material layer contains the above-mentioned second negative electrode active material, so that the advantage of fast charging can be exerted as it is. In particular, the second negative electrode active material includes one or more selected from the group consisting of carbon-based active materials, silicon-based active materials, metal-based active materials that can form alloys with lithium, and lithium-containing nitrides, so that the irreversibility is high, which is also beneficial even in the pre-lithiation process of pre-charging the negative electrode. Compared with the case where only the first negative electrode active material layer is simply applied, the second negative electrode active material layer contains the second negative electrode active material having the above-mentioned composition, which can perform a uniform pre-lithiation process on the upper part of the negative electrode, thereby extending the life.

[0202] In the exemplary embodiment of the present application, the porosity of the first and second negative electrode active material layers may satisfy the range of 10% or more and 60% or less.

[0203] In another exemplary embodiment, the porosity of the first and second negative electrode active material layers may satisfy a range of 10% or more and 60% or less, preferably 20% or more and 50% or less, more preferably 30% or more and 45% or less.

[0204] The porosity varies depending on the composition and content of the active material, the conductive material, and the binder contained in the first and second negative electrode active material layers, and thus the electrode has conductivity and resistance within appropriate ranges.

[0205] An exemplary embodiment of the present application provides a lithium secondary battery including: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator disposed between the positive electrode and the negative electrode; and an electrolyte.

[0206] The secondary battery according to the exemplary embodiment of the present specification may particularly include the above-mentioned negative electrode for lithium secondary battery. Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte, and the negative electrode is the same as the above-mentioned negative electrode. Since the negative electrode has been described above, its detailed description is omitted.

[0207] The positive electrode may include a positive electrode collector layer and a positive electrode active material layer formed on the positive electrode collector layer and including a positive electrode active material.

[0208] In the positive electrode, there is no particular restriction on the positive electrode collector layer, as long as it has conductivity and does not cause chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, fired carbon; or aluminum or stainless steel, etc., each of which is surface-treated with carbon, nickel, titanium, silver, etc. In addition, the positive electrode collector layer can generally have a thickness of 3 to 500 μm, and the surface of the collector can be formed with fine concave-convex to enhance the adhesion of the positive electrode active material. For example, the positive electrode collector can be used in various forms such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.

[0209] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may be: a layered compound such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2) or a compound replaced by one or more transition metals; a lithium iron oxide such as LiFe3O4; a lithium manganese oxide such as Li 1+c1 Mn 2-c1 O4 (0≤c1≤0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5 and Cu2V2O7; 1-c2 M c2 Ni-site lithium nickel oxide represented by the chemical formula LiMn 2-c3 M c3 Lithium manganese composite oxide represented by Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn and Ta, and satisfies 0.01≤c3≤0.1); LiMn2O4 in which a part of Li in the chemical formula is replaced by alkaline earth metal ions, etc., but not limited thereto. The positive electrode can be Li metal.

[0210] The positive electrode active material layer may further include a positive electrode conductive material and a positive electrode binder in addition to the positive electrode active material.

[0211] In this case, the positive electrode conductive material is used to provide conductivity to the electrode, and can be used without particular limitation as long as the positive electrode conductive material has electronic conductivity without causing chemical changes in the battery to be constructed. Specific examples may include: graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, etc., and any one of them or a mixture of two or more thereof may be used.

[0212] In addition, the positive electrode binder is used to improve the bonding between the positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode collector. Specific examples may include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber or its various copolymers, and any one thereof or a mixture of two or more thereof may be used.

[0213] The separator is used to separate the negative electrode from the positive electrode and provide a path for the movement of lithium ions. As the separator, any separator can be used without particular limitation, as long as the separator is generally used in a secondary battery. In particular, a separator having a high moisture retention capacity for electrolytes and low resistance to electrolyte ion migration can be preferably used. Specifically, a porous polymer film, such as a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer; or a laminated structure having two or more layers thereof can be used. In addition, a common porous non-woven fabric can be used, such as a non-woven fabric formed of a high melting point glass fiber, a polyethylene terephthalate fiber, and the like. In addition, a coated separator comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a separator having a single-layer or multilayer structure can be selectively used.

[0214] Examples of the electrolyte may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, or a molten-type inorganic electrolyte that may be used in manufacturing a lithium secondary battery, but are not limited thereto.

[0215] Specifically, the electrolyte may include a nonaqueous organic solvent and a metal salt.

[0216] As the nonaqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate or ethyl propionate can be used.

[0217] Especially, in carbonate system organic solvent, ethylene carbonate and propylene carbonate as cyclic carbonate are high viscosity organic solvents and have high dielectric constant to dissociate lithium salt well, therefore can preferably use.When cyclic carbonate and linear carbonate with low viscosity and low dielectric constant such as dimethyl carbonate and diethyl carbonate are mixed with appropriate ratio and used, can prepare electrolyte with high conductivity, therefore can more preferably use.

[0218] A lithium salt may be used as the metal salt, and the lithium salt is a material that is easily soluble in a non-aqueous electrolyte, wherein, for example, as an anion of the lithium salt, one or more species selected from the group consisting of: F - , Cl - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - .

[0219] In the electrolyte, in order to improve the life characteristics of the battery, inhibit the reduction of the battery capacity, increase the discharge capacity of the battery, etc., in addition to the above-mentioned electrolyte components, one or more additives such as the following may be included: halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme dimethyl ether, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum trichloride.

[0220] An exemplary embodiment of the present invention provides a battery module including a secondary battery as a unit cell and a battery pack including the battery module. Since the battery module and the battery pack include secondary batteries having high capacity, high rate capability, and high cycle characteristics, the battery module and the battery pack can be used as a power source for medium and large devices selected from the group consisting of: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0221] Mode for the Invention

[0222] Hereinafter, preferred embodiments will be provided to better understand the present invention. It will be apparent to those skilled in the art that embodiments are provided only to illustrate the present invention, and various modifications and changes may be made within the scope of the present invention and within the scope of the technical spirit. Such modifications and changes naturally fall within the scope of the claims included herein.

[0223] <Preparation Example>

[0224] <Preparation of negative electrode>

[0225] Example 1

[0226] Preparation of the first negative electrode active material layer

[0227] As the silicon-based active material, Si (average particle size (D 50 ): 5 μm), the first conductive material, the second conductive material and polyacrylamide as a binder were added to distilled water as a solvent for forming a negative electrode slurry at a weight ratio of 80:9.5:0.5:10 to prepare a first negative electrode slurry (solid concentration: 25 wt %).

[0228] The first conductive material is plate-like graphite (specific surface area: 17 m 2 / g, average particle size (D 50 ): 3.5 μm), and the second conductive material is SWCNT.

[0229] As a mixing method, after the first conductive material, the second conductive material, the binder, and water were dispersed with a homomixer at 2500 rpm for 30 minutes, the active material was added to the dispersion and then dispersed at 2500 rpm for 30 minutes to prepare slurry.

[0230] 50 to 70 mg / 25 cm 2The first negative electrode slurry was coated on both surfaces of a copper current collector (thickness: 8 μm) as a negative electrode current collector, and then roll-pressed and dried in a vacuum oven at 130° C. for 10 hours to form a first negative electrode active material layer.

[0231] Preparation of the second negative electrode active material layer

[0232] SiO (average particle size (D 50 ): 3.5 μm), a first conductive material, a second conductive material and polyacrylamide as a binder, a second negative electrode active material layer composition was prepared, and a second negative electrode slurry (solid concentration: 25 wt %) was prepared by adding the composition to distilled water as a solvent for forming a negative electrode slurry.

[0233] The first conductive material is plate-like graphite (specific surface area: 17 m 2 / g, average particle size (D 50 ): 3.5 μm), and the second conductive material is carbon nanotubes.

[0234] As a mixing method, after the first conductive material, the second conductive material, the binder, and water were dispersed with a homomixer at 2500 rpm for 30 minutes, the active material was added to the dispersion and then dispersed at 2500 rpm for 30 minutes to prepare slurry.

[0235] 15 to 40 mg / 25 cm 2 The second negative electrode slurry was coated on the first negative electrode active material layer in an amount of 150 Å, and then roll-pressed and dried in a vacuum oven at 130° C. for 10 hours to form a second negative electrode active material layer (thickness: 15 μm).

[0236] In this case, the core thickness of the coater and the liquid thickness (thickness of the coating liquid) are shown in Table 1 below, and the corresponding Formula 1 is also shown in Table 1 below.

[0237]

[0238] <Preparation of Secondary Battery>

[0239] By using LiNi as the positive electrode active material 0.6 Co 0.2 Mn 0.2 O2 (average particle size (D 50): 15 μm), carbon black (product name: Super C65, manufacturer: Timcal) as a conductive material and polyvinylidene fluoride (PVdF) as a binder were added to N-methyl-2-pyrrolidone (NMP) as a solvent for forming a positive electrode slurry in a weight ratio of 97:1.5:1.5 to prepare a positive electrode slurry (solid concentration: 78 wt %).

[0240] The positive electrode slurry was prepared at 537 mg / 25 cm 2 The positive electrode was prepared by coating the positive electrode active material layer (thickness: 65 μm) with a loading amount of 240 μm on both surfaces of an aluminum current collector (thickness: 12 μm) serving as a positive electrode current collector, and then roll-pressing the same and drying it in a vacuum oven at 130°C for 10 hours to form a positive electrode active material layer (thickness: 65 μm), thereby preparing a positive electrode (positive electrode thickness: 77 μm, porosity: 26%).

[0241] A lithium secondary battery was manufactured by inserting a polyethylene separator between the positive electrode and the negative electrode of the example and the comparative example, and injecting an electrolyte.

[0242] The electrolyte was obtained by adding 3 wt % of vinylene carbonate based on the total weight of the electrolyte to an organic solvent in which fluoroethylene carbonate (FEC) and diethyl carbonate (DMC) were mixed in a volume ratio of 30:70, and then adding LiPF6 as a lithium salt to a concentration of 1 M.

[0243] Experimental Example 1: Evaluation of Lifespan Characteristics

[0244] For the secondary battery containing the negative electrode manufactured in the embodiment and the comparative example, the life and capacity retention rate were evaluated using an electrochemical charge and discharge device. The secondary battery was subjected to an in-situ cycle test at 4.2-3.0 V 1C / 0.5C, and during the test, 0.33C / 0.33C charge and discharge (4.2-3.0 V) was performed every 50 cycles to measure the capacity retention rate. In Table 2 below, the in-situ capacity retention rate is shown instead of the RPT capacity retention rate.

[0245] Capacity retention rate (%) = {(discharge capacity at the Nth cycle) / (discharge capacity at the first cycle)} × 100

[0246] Experimental Example 2: Evaluation of resistance increase rate measurement

[0247] In the test of Experimental Example 1, after the battery was charged and discharged at 0.33C / 0.33C (4.2-3.0V) every 50 cycles to measure the capacity retention rate, the battery was discharged at 2.5C pulse at SOC 50 to measure the resistance, thereby comparing and analyzing the resistance increase rate.

[0248] Furthermore, for the evaluation of the life characteristics and the evaluation of the resistance increase rate measurement, data at the time of 200 cycles were calculated, respectively, and the results are shown in Table 2 below.

[0249]

[0250] It can be seen from Tables 1 and 2 that in the case of the negative electrode according to the embodiment of the present application, the second negative electrode active material layer satisfies the non-uniformity of the above formula 1. In other words, the first negative electrode active material layer has a silicon-based negative electrode and is coated in a thin thickness range. In this case, there is a problem when the second negative electrode active material layer is formed in the form of a thin film on the silicon-based negative electrode. However, when coated by the method in Table 1 (by controlling the liquid thickness and core thickness of the coating machine), the non-uniformity of the above formula 1 is satisfied, and the second negative electrode active material layer can be more uniformly and thinly coated on the first negative electrode active material layer.

[0251] From this, it was confirmed that the lithium secondary battery including the negative electrode had the best capacity characteristics (which is an advantage of the Si negative electrode) and improved cycle characteristics and resistance increase rate.

[0252] In the case of Comparative Example 1 and Comparative Example 2, both are beyond the scope of Formula 1 of the present application. That is, the structure in which the second negative electrode active material layer is formed is the same, but the coating is uneven compared with Examples 1 to 4. In this case, it can be confirmed that the capacity and life can be improved compared with the general negative electrode with a single-layer structure, but the capacity retention rate and resistance increase rate are not good enough compared with Examples 1 to 4 of the present application. This corresponds to the result that the second negative electrode active material layer as a buffer layer is unevenly coated on the first negative electrode active material layer.

Claims

1. A negative electrode for a lithium secondary battery, the negative electrode comprising: A negative electrode current collector layer; a first negative electrode active material layer, the first negative electrode active material layer being disposed on one surface or both surfaces of the negative electrode current collector layer; and a second negative electrode active material layer provided on a surface of the first negative electrode active material layer opposite to a surface facing the negative electrode current collector layer, wherein the first negative electrode active material layer contains a first negative electrode active material layer composition comprising a first negative electrode active material, and the second negative electrode active material layer contains a second negative electrode active material layer composition comprising a second negative electrode active material, wherein the first negative electrode active material comprises one or more selected from the group consisting of SiOx (x=0) and SiOx (0<x<2), and based on 100 parts by weight of the first negative electrode active material, comprises 95 parts by weight or more of SiOx (x=0), wherein the second negative electrode active material comprises one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of forming an alloy with lithium, and a lithium-containing nitride, wherein the second negative electrode active material layer has a first surface of the second negative electrode active material layer opposite to a surface facing the first negative electrode active material layer and a second surface of the second negative electrode active material layer facing the first negative electrode active material layer, wherein the first surface and the second surface each comprise an uneven surface, and The second negative electrode active material layer satisfies the non-uniformity shown by the following formula 1: [Formula 1] 0 μm≤│C-(A+B) / 2│≤10 μm In formula 1, A represents the longest distance between the first surface and the second surface (μm), B represents the shortest distance between the first surface and the second surface (μm), and C represents the average thickness (μm) of the second negative electrode active material layer.

2. The negative electrode for a lithium secondary battery according to claim 1, wherein A is 5 μm or more and 25 μm or less, and Here, C is greater than or equal to 5 μm and less than or equal to 20 μm. 3 . The negative electrode for a lithium secondary battery according to claim 1 , wherein an average thickness of the second negative electrode active material layer is 10% or more and 40% or less of the total thickness of the first negative electrode active material layer and the second negative electrode active material layer. 4 . The negative electrode for a lithium secondary battery according to claim 1 , wherein the average surface roughness (Sa) of the first surface is 700 nm or less.

5. A negative electrode for a lithium secondary battery according to claim 1, wherein the second negative electrode active material comprises one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of forming an alloy with lithium, and a lithium-containing nitride, and based on 100 parts by weight of the second negative electrode active material, the content of the silicon-based active material is 50 parts by weight or more and 100 parts by weight or less.

6. The negative electrode for a lithium secondary battery according to claim 1, wherein the silicon-based active material comprises one or more selected from the group consisting of SiOx (0 < x < 2), SiC, and Si alloy.

7. The negative electrode for a lithium secondary battery according to claim 1, wherein the silicon-based active material comprises SiOx (0 < x < 2).

8. The negative electrode for a lithium secondary battery according to claim 1, wherein based on 100 parts by weight of the first negative electrode active material layer composition, the content of the first negative electrode active material is 60 parts by weight or more.

9. The negative electrode for a lithium secondary battery according to claim 1, wherein the viscosity of the first negative electrode active material layer composition is a shear viscosity of 2,000 cPs or more and 15,000 cPs or less at a shear rate of 2.5 (1 / s), and wherein the viscosity of the second negative electrode active material layer composition is lower than the viscosity of the first negative electrode active material layer composition.

10. The negative electrode for a lithium secondary battery according to claim 1, wherein the first negative electrode active material layer is formed on the entire surface of the negative electrode current collector layer, and wherein the second negative electrode active material layer is formed on the entire surface of the first negative electrode active material layer.

11. A method for manufacturing a negative electrode for a lithium secondary battery, the method comprising: preparing a negative electrode current collector layer; forming a first negative electrode active material layer by coating a first negative electrode active material layer composition onto one or both surfaces of the negative electrode current collector layer using a coater; and forming a second negative electrode active material layer by coating a second negative electrode active material layer composition onto the surface of the first negative electrode active material layer opposite to the surface in contact with the negative electrode current collector layer using a coater, wherein the first negative electrode active material comprises one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the first negative electrode active material, comprises 95 parts by weight or more of SiOx (x = 0), wherein the second negative electrode active material comprises one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of forming an alloy with lithium, and a lithium-containing nitride, wherein when forming the first negative electrode active material layer by coating the first negative electrode active material layer composition, the liquid thickness of the coater is 50 μm or more and 100 μm or less, and wherein when forming the second negative electrode active material layer by coating the second negative electrode active material layer composition onto the surface of the first negative electrode active material layer opposite to the surface in contact with the negative electrode current collector layer, the liquid thickness of the coater is 10 μm or more and 60 μm or less.

12. The method according to claim 11, wherein the core thickness of the coater is 0.4T or more and 2T or less.

13. The method according to claim 11, comprising pre-lithiation of the negative electrode having the first negative electrode active material layer and the second negative electrode active material layer formed on the negative electrode current collector, The pre-lithiation of the negative electrode includes a lithium electroplating process, a lithium metal transfer process, a lithium metal deposition process or a stabilized lithium metal powder (SLMP) coating process.

14. The method according to claim 11, wherein forming the second negative active material layer on the first negative active material layer comprises a wet-on-dry process, and The wet-to-dry process comprises: applying the first negative electrode active material layer composition; forming the first negative electrode active material layer by partially or completely drying the coated first negative electrode active material layer composition; and The second negative active material layer composition is applied to the first negative active material layer.

15. The method according to claim 11, wherein forming the second negative electrode active material layer on the first negative electrode active material layer comprises a wet-on-wet process, and The wet-on-wet process comprises: applying the first negative electrode active material layer composition; and The second negative electrode active material layer composition is applied to the first negative electrode active material layer composition in a state where the first negative electrode active material layer composition is not dried.

16. A lithium secondary battery, comprising: positive electrode; The negative electrode for a lithium secondary battery according to any one of claims 1 to 10; A separator disposed between the positive electrode and the negative electrode; and Electrolytes.

Citation Information

Patent Citations

  • Anode for lithium ion battery

    JP2009080971A